Consistency evaluation of lung adenocarcinoma tissue and circulating tumor cells related gene mutation detection based on multi-site immunomagnetic beads. (April 2022) - Xue, Keying; Luo, Bingqing; Li, Xiaoqing; Deng, Weixian; Zeng, Chunyan; Zuo, Cuiyun
This study was designed to investigate the feasibility of genetic testing using circulating tumor cells (CTCs) instead of tumor tissues in lung adenocarcinoma to break through its limitation. Separation system for epithelial cell adhesion molecule (EpCAM), epidermal growth factor receptor (EGFR), and Vimentin expressing CTCs was constructed and used to capture CTCs in the blood samples of 57 patients with lung adenocarcinoma. Genetic mutations of genes involved in targeted therapies were detected by next-generation sequencing (NGS) in tissues from these patients. Blood CTC samples with the gene mutations identified by tissue-NGS were selected and corresponding gene mutations were detected by Sanger sequencing. The specificity of the CTC separation system was 95.48% and the sensitivity was 90.85%. The average number of CTCs in the blood of patients with lung adenocarcinoma was 12.47/7.5 mL. Comparison of the tissue-NGS with the CTC-Sanger sequencing showed that the consistencies of genetic mutations of EGFR ( n = 24), KRAS ( n = 9), TP53 ( n = 19), BRAF ( n = 1), ERBB2 ( n = 2), and PIK3CA ( n = 3) were 92.31%, 75.00%, 86.36%, 50.00%, 66.67%, and 75.00%, with an overall consistency of 84.06%. The CTC separation system established in this study shows high specificity and sensitivity. CTCs can be used as a suitable alternative to tumor tissues that are difficult to obtain in clinical practice and overcome the difficulties in tumor tissue collection, which is of significance in guiding clinical medication and individualized treatment with significant clinical application value in terms of genetic testing for targeted therapies in tumor treatment.